Crossing the threshold of empire: from ship to shore in colonial Madras, 1750-1895 - Breene, M (2023)
This thesis examines the process of moving between ship and shore at the English East India Company port of Madras (Chennai) between 1750 and 1895. It argues that while the history of technology in the British empire has largely focused on the deployment of Western innovations, the daily administration of empire was instead dependent on indigenous technologies and practitioners. Madras’s dangerous littoral environment meant that trade was facilitated by masula boats and catamarans, built, manned, and owned by skilled local boatmen.